The activation of cGAS-STING pathway offers novel therapeutic opportunities in cancers - Wang, Yumin; Zhu, Yonglin; Cao, Yuwei; Li, Yulin; Zhang, Zhe; Fleishman, Joshua S.; Cheng, Sihang; Chen, Jichao; Ding, Mingchao (Frontiers in immunology, 2025)
The cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) pathway are crucial elements of the type I interferon (type I IFN) response. cGAS senses both exogenous and endogenous DNA within cells, labeling cGAS-STING as a pivotal anti-tumor immunity mechanism, autoimmunity, sterile inflammatory responses, and cellular senescence. The cGAS-STING pathway, a pivotal innate immune axis, modulates tumorigenesis via diverse effector responses. Emerging evidence have shown that activating of cGAS-STING pathway functions as a therapy to kill cancers. Insights into the biology of the cGAS-STING pathway have enabled the discovery of small-molecule agents which have the potential to activate cGAS-STING axis in cancers. In this review, we first outline the principal components of the cGAS-STING signaling cascade. Then we explore recent advancements in understanding the cGAS-STING signaling pathway, with particular emphasis on its activation mechanisms and roles in tumor cancer killing. Next, we summarize a list of bioactive small-molecule compounds which activate the cGAS-STING axis, reviewing their potential applications. Finally, we discuss key limitations of this new proposed therapeutic approach and provide possible techniques to overcome them. This review highlights a novel groundbreaking therapeutic possibilities through activating cGAS-STING in cancers.